Uma nova raça fisiológica de Puccinia kuehnii virulenta a variedade RB966928 - Morais, Giovana Cabello de (Universidade Federal de São Carlos, 2024)
Brazil is currently the largest sugarcane producer in the world, reaching 677.6 million tons of processed sugarcane in the 2022/23 harvest, the main products of which are ethanol and sugar. In order to meet the entire demand of the sector, it is extremely important to maintain high productivity in the field, and one of the main obstacles would be the presence of diseases in the field, one of the main ones being orange rust. It is a disease caused by a fungus Puccinia kuehnii, which is characterized by high dissemination and is responsible for reducing the photosynthetic area of ​​the plant, reducing its productivity. Its main control method is the adoption of resistant varieties, however in some cases this resistance can be broken, potentially causing major losses to the sector. Therefore, the present work aimed to: I. Phenotypically evaluate whether P. kuehnii manifested in the variety RB966928 is a new physiological race. II. If objective I is proven, evaluate whether there is a microsatellite molecular marker capable of differentiating the different physiological races tested. The first part of the work was conducted in a closed environment, with light and climate controlled, the design was randomized blocks, where two varieties (RB966928 and SP89-1115) and two isolates of different origin (ScPk01-207 and ScPk20-01) were tested. , with 5 repetitions per treatment, carried out in duplicate. Moving on to the molecular part, extracting DNA from a pustule per inoculated plant, and its analysis carried out through PCR, followed by electrophoresis. The evaluation of the first part was carried out at 14, 21, 28 and 35 days after inoculation of the treatments, carrying out an analysis of the percentage of affected area, and at 28 days an analysis of the viability of the urediniospores was carried out. The work concluded the existence of a new physiological race of virulent P. kuehnii, the variety RB966928, which presented a percentage of affected leaf area greater than 1%, and its spores proved to be viable. In the second part, it was not possible to identify an SSR capable of demonstrating a genetic difference between the isolates evaluated.
A new physiological race of Puccinia kuehnii virulent variety RB966928
Keywords: Cana-de-açúcar; Puccinia kuehnii; variedade resistente; raça fisiológica; RB966928; Sugarcane; Physiological race; Resistant variety; CIENCIAS AGRARIAS::AGRONOMIA